Study the lead (Pb) removal from synthetic Wastewater by activated carbon from rubber seed shell by activation with ZnCl2 - KEOMEESAY, PHIDSAVARD (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research was to study the lead (Pb) removal from synthetic wastewater by activated carbon from rubber seed shell by activation with ZnCl2. The effects of the preparation variable, which was impregnation ratio (ZnCl2: rubber seed shell), activation temperature, and activation time. This studying was to compare the iodine number and to select the best suitable condition for activated carbons and the efficiency for lead removal from synthetic wastewater by using each kind of activated carbon was also studied. The result was found that the activated carbon was suitable with activating by ZnCl2 using the ratio of rubber seed shell : ZnCl2 = 1:1 at activating temperature 800 for 1 hr. Then washed the residue of activated carbons was with hot water and distilled water. The iodine number of activated carbon was 1113.1 mg/g, the surface area was 1574.46 m2/g, respectively. The efficiency for lead removal at pH 6, 7, 8, and 9 were 99.77%, 99.92%, 99.65%, and 99.92% for activated carbon with activating by ZnCl2, respectively. From the preparation of activated carbon from agriculture wastes studies, it was found that activated carbon from rubber seed shell rind had the potential that could be developed for household as well as industrial use.